Configurable Multi‐Stable Surface Topographies: Re‐ and Preconfigurable Multistable Visible Light Responsive Surface Topographies (Small 50/2018). Issue 50 (13th December 2018) - Hendrikx, Matthew; ter Schiphorst, Jeroen; van Heeswijk, Ellen P. A.; Koçer, Gülistan; Knie, Christopher; Bléger, David; Hecht, Stefan; Jonkheijm, Pascal; Broer, Dirk J.; Schenning, Albertus P. H. J.
Abstract : In article number1803274, Dirk J. Broer, Albertus P. H. J. Schenning, and co‐workers fabricate multi‐stable, re‐ and pre‐configurable visible light responsive surface topographies by using low illumination doses. Preliminary studies reveal that these light responsive polymers are suitable as adaptive biological surfaces. The authors would like to thank Karel Haesevoets for the cover design and the ICMS for the creation of the image.